2021
DOI: 10.21508/1027-4065-2020-65-6-29-33
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Fatty Acid Binding Protein as the Promising Marker of Small Intestine Permeability

Abstract: The Article provides the literature data on the possibilities to use the intestinal protein binding the fatty acids as the diagnostic marker for the intestinal injuries of different etiology. Aspects of the marker use for the celiac disease are considered. The information on the results of use of the various diagnostic techniques for the celiac disease compared with the definition of the intestinal protein binding the fatty acids is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[ 6 ] Other studies on i-FABP have already shown that during haemolysis, the release of free haemoglobin causes intravascular NO absorption, which leads to impaired organ perfusion with subsequent tissue injury and increased i-FABP levels. [ 7 8 9 10 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Other studies on i-FABP have already shown that during haemolysis, the release of free haemoglobin causes intravascular NO absorption, which leads to impaired organ perfusion with subsequent tissue injury and increased i-FABP levels. [ 7 8 9 10 11 ]…”
Section: Discussionmentioning
confidence: 99%